Dysregulated cellular functions and cell stress pathways provide critical cues for activating and targeting natural killer cells to transformed and infected cells. Issue 1 (13th October 2017) - Raulet, David H.; Marcus, Assaf; Coscoy, Laurent
Summary: Natural killer (NK) cells recognize and kill cancer cells and infected cells by engaging cell surface ligands that are induced preferentially or exclusively on these cells. These ligands are recognized by activating receptors on NK cells, such as NKG2D. In addition to activation by cell surface ligands, the acquisition of optimal effector activity by NK cells is driven in vivo by cytokines and other signals. This review addresses a developing theme in NK cell biology: that NK‐activating ligands on cells, and the provision of cytokines and other signals that drive high effector function in NK cells, are driven by abnormalities that arise from transformation or the infected state. The pathways include genomic damage, which causes self DNA to be exposed in the cytosol of affected cells, where it activates the DNA sensor cGAS. The resulting signaling induces NKG2D ligands and also mobilizes NK cell activation. Other key pathways that regulate NKG2D ligands include PI‐3 kinase activation, histone acetylation, and the integrated stress response. This review summarizes the roles of these pathways and their relevance in both viral infections and cancer.